DEVELOPMENT OF CONSTRUCTION AND ITS IMPACT ON THE ENVIRONMENT UNDER MARTIAL LAW (Innovative professional education, 2024)
The necessity state ecology and construction industry in the martial state, construction development and its influence on the ecological component.
Keywords: ecology, construction industry, environment, the concept of sustainable, The State building regulations, professional education